Accessibility in the realities of everyday life: Social Pedagogy in the construction of the right to inclusive education - Gradaille Pernas, Rita; Caride Gómez, José Antonio (Education Policy Analysis Archives, 2016)
Human Rights represents a common framework for the development of communities and individuals in conditions of freedom, justice and equality; therefore, it is necessary to implement strategies —from Education-Social Pedagogy— that promote greater accessibility in the exercise of this right to education. This accessiblity ensures —putting emphasis on an expanded vision of education— the same opportunities in everyday life for all people and builds a truly inclusive education: not only a method or pedagogical principle, but also an alternative way of living, training to deal with diversity, and an integration of teaching and learning with everyday life.